Essential Fatty Acid Assimilation and Synthesis in Larvae of the Bivalve Crassostrea gigas - Costa, Fiz,; Robert, René; Quéré, Claudie; Wikfors, Gary H.; Soudant, Philippe (Lipids, 2015)
Essential fatty acids (EFA) are important for bivalve larval survival and growth. The purpose of this study was to quantitatively assess for the first time through a mass-balance approach dietary EFA incorporation and synthesis within Crassostrea gigas larvae. A first experiment was carried out using two microalgae, Tisochrysis lutea (T) and Chaetoceros neogracile (Cg), as mono- and bi-specific diets. A second experiment using a similar design was performed to confirm and extend the results obtained in the first. Flow-through larval rearing was used for accurate control of food supply and measurement of ingestion. Non-methylene-interrupted fatty acids were synthetized from precursors supplied in the diet: 16:1n-7 and 18:1n-9, mediated by Delta 5 desaturase. Moreover, this Delta 5 desaturase presumably allowed larvae to convert 20:3n-6 and 20:4n-3 to 20:4n-6 and 20:5n-3, respectively, when the product EFA were poorly or not supplied in the diet, as when larvae were fed T exclusively. Under our experimental conditions, none of the diets induced 22:6n-3 synthesis; however, 22:6n-3 incorporation into larval tissues occurred selectively under non-limiting dietary supply to maintain optimal levels in the larvae. This combination of flow-through larval rearing and biochemical analysis of FA levels could be applied to additional dietary experiments to precisely define optimal levels of EFA supply.